2018
DOI: 10.1016/j.euroneuro.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Can we increase speed and efficacy of antidepressant treatments? Part I: General aspects and monoamine-based strategies

Abstract: Major depressive disorder (MDD) is a severe psychiatric syndrome with high prevalence and socioeconomic impact. Current antidepressant treatments are based on the blockade of serotonin (5-hydroxytryptamine, 5-HT) and/or noradrenaline transporters. These drugs show slow onset of clinical action and limited efficacy, partly due to the activation of physiological negative feed-back mechanisms operating through autoreceptors (5-HT, 5-HT, α-adrenoceptors) and postsynaptic receptors (e.g., 5-HT). As a result, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 123 publications
0
48
0
1
Order By: Relevance
“…For example, in depressed patients with the HTR1A rs6295 polymorphism and/or showing increased raphe 5-HT 1A autoreceptors, as seen in depressed males and at-risk offspring, 200,201 a strategy to block these receptors (e.g., using SSRI with pindolol or vortioxetine), or bypass presynaptic 5-HT by directly targeting postsynaptic 5-HT 1A receptors or by targeting other monoamines (e.g., noradrenaline, using SNRIs, tricyclic antidepressants) may be more efficient than SSRI treatment alone. 11 In the future, directly targeting the 5-HT 1A autoreceptor using intranasal 5-HT 1A siRNA conjugated to SSRI for raphe targeting could be used for knockdown 5-HT 1A receptor RNA. 186 One can envisage screening patients' blood samples for depression-related miRNAs and then targeting those brain miRNAs using intranasal therapeutics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in depressed patients with the HTR1A rs6295 polymorphism and/or showing increased raphe 5-HT 1A autoreceptors, as seen in depressed males and at-risk offspring, 200,201 a strategy to block these receptors (e.g., using SSRI with pindolol or vortioxetine), or bypass presynaptic 5-HT by directly targeting postsynaptic 5-HT 1A receptors or by targeting other monoamines (e.g., noradrenaline, using SNRIs, tricyclic antidepressants) may be more efficient than SSRI treatment alone. 11 In the future, directly targeting the 5-HT 1A autoreceptor using intranasal 5-HT 1A siRNA conjugated to SSRI for raphe targeting could be used for knockdown 5-HT 1A receptor RNA. 186 One can envisage screening patients' blood samples for depression-related miRNAs and then targeting those brain miRNAs using intranasal therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…They are thought to involve reduced serotonin (5-HT) activity, [3][4][5][6] which is reversed by selective serotonin reuptake inhibitors (SSRIs) such as fluoxetine. [7][8][9][10][11] However, treatment with SSRIs for 5 to 8 weeks is required for remission, which occurs in only 30% of patients. [12][13][14] Thus, although the serotonin system is involved in major depression and antidepressant actions, a better understanding of how the system is regulated over time is needed to further enhance the effectiveness of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in 5‐HT transmission within the mPFC have been specifically associated with suicidal intent and negative affective bias in clinical imaging studies (Leyton et al., ; Robinson et al., ). Notably, increasing 5‐HT transmission in mPFC is associated with antidepressant efficacy of selective serotonin reuptake inhibitors (Artigas, Bortolozzi, & Celada, ), ketamine (Pham et al., ), and deep brain stimulation (Veerakumar et al., ) in rodent models.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of physiological negative feedback mechanisms operating through auto-receptors (5-HT1A, 5-HT1B, α2-adrenoceptors) and postsynaptic receptors (e.g., 5-HT3) may account for the delayed onset of antidepressant treatment response. While it has been reported that mixed ß-adrenoceptor/5-HT1A antagonists as pindolol would accelerate the response of antidepressants[47], especially in the case of selective serotonin reuptake inhibitors (SSRIs)[48], the role of 5HT-1 and 5HT2 receptors in the development of tolerance to drugs for depression has been likewise postulated[2]. It has been hypothesized that some neurobiological mechanisms related to the therapeutic effects of drugs for depression (e.g.…”
mentioning
confidence: 99%